Advances in carbon capture, utilization and storage. (15th November 2020) - Zhang, Zhien; Wang, Tao; Blunt, Martin J.; Anthony, Edward John; Park, Ah-Hyung Alissa; Hughes, Robin W.; Webley, Paul A.; Yan, Jinyue
Abstract: Carbon Capture, Utilization and Storage (CCUS) is one of the essential components for mitigating CO2 emissions. This special issue of Applied Energy includes research and review articles on CCUS technologies and applications. Recent developments in CO2 capture technologies with emphasis on post-combustion processes are highlighted. CO2 utilization in fuel production and other chemical processes, and CO2 storage are also presented, along with detailed discussion of life cycle assessments and techno-economic analyses to evaluate the various CCUS processes.